2008
DOI: 10.1042/bst0361482
|View full text |Cite
|
Sign up to set email alerts
|

Lectin–epithelial interactions in the human colon

Abstract: Similar changes in glycosylation occur in the colonic epithelium in inflammatory conditions such as ulcerative colitis and Crohn's disease and also in colon cancer and precancerous adenomatous polyps. They include reduced length of O-glycans, reduced sulfation, increased sialylation and increased expression of oncofetal carbohydrate antigens, such as sialyl-Tn (sialylalpha2-6GalNAc), and the TF antigen (Thomsen-Friedenreich antigen) Galbeta1-3GalNAcalpha-Ser/Thr. The changes affect cell surface as well as secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…More recently, Fakhry et al (2009) observed that rod-shaped bacteria identified as B. breve bound tightly to the biopsied human ileal epithelium. Human cells, including gastro-intestinal epithelial cells, are known to express a variety of carbohydrate antigens (or lectin-binding sites) on their surface (Boland and Roberts 1988;Rhodes et al 2008). Meanwhile, mucins secreted from human intestinal epithelia are glycoproteins that also express various oligosaccharide structures branching off from their peptide stems.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Fakhry et al (2009) observed that rod-shaped bacteria identified as B. breve bound tightly to the biopsied human ileal epithelium. Human cells, including gastro-intestinal epithelial cells, are known to express a variety of carbohydrate antigens (or lectin-binding sites) on their surface (Boland and Roberts 1988;Rhodes et al 2008). Meanwhile, mucins secreted from human intestinal epithelia are glycoproteins that also express various oligosaccharide structures branching off from their peptide stems.…”
Section: Discussionmentioning
confidence: 99%
“…These include shortened oligosaccharide chain length, reduced sulphation, increased sialylation and increased expression of short oncofoetal carbohydrate antigens such as Thomsen-Friedenreich (TF) antigen (galactose β-1,3-N-acetylgalactosamine-α-Ser/Thr) and sialylTn (sialyl α-2,6- N-acetylgalactosamine-α-Ser/Thr) [reviewed in ref. [20]]. These changes are not unique to UC though and also occur in CD and in colon cancer and adenomatous as well as hyperplastic polyps.…”
Section: Alterations In the Mucosal Barrier In Inflammatory Bowel Dismentioning
confidence: 99%
“…Alternatively, increased sialylation of TF antigen and of the more peripheral Lewis structures has been shown to be present in colon cancer metastases in comparison with primary tumours from the same individuals (Bresalier et al, 1996). There is increasing evidence that alterations of cancer-associated glycosylation may play an important regulatory role in cancer progression and development as a result of altered interaction of the cells with carbohydrate-binding lectins from endogenous as well as exogenous sources (Rhodes et al, 2008). Recent studies have shown that the increased expression of TF antigen on cancer-associated MUC1 allows binding of galectin-3 to the cancer cells (Khaldoyanidi et al, 2003;Yu et al, 2007).…”
Section: Disease-related Changes In Mucin and Mucosal Glycosylation Cmentioning
confidence: 99%